KARAKTERISTIK STATUS GIZI DAN HUBUNGANNYA DENGAN BERBAGAI FAKTOR DETERMINAN PADA ANAK USIA 12-36 BULAN DARI KELUARGA SOSIO-EKONOMI MENENGAH KE ATAS - Jajah K. Husaini; Abas B. Jahari (Persagi, 2007)
NUTRITIONAL STATUS CHARACTERISTICS AND ITS RELATED DETERMINANT FACTORS AMONG HEALTHY CHILDREN AGED 12-36 MONTHS FROM MIDDLE UP SOCIO-ECONOMIC STATUS.Background: There are very few studies had been carried out among children from middle up socio-economy status, and therefore, the prevalence of malnutrition as well as characteristics of nutritional status of children from middle upper socioeconomic families have not been well reported. Objectives: To describe the nutritional status of children from well being families, and its related determinant factors.Methods: A total of 235 children aged 12-36 months from middle upper socio-economic status in Bogor city, West Java had been studied. The cross-sectional study design was implemented. Data on general characteristics of the families and anthropometric measurements on both the child and the mother were collected by well trained field workers. Results: The study reveals that the average birth weight was 3.2 ± 0.41 kg and birth length was 49.2 ± 1.96 cm. Most mothers (43.2%) breastfed their children until 3 months, 22.0% less than 3 months and the remaining 34,8% above 3 months. Using NCHS standard, underweight was found 6.1%, stunting was 4.2%, and wasting was 2.8%, There were no subjects with Z-score above 2 SD of weight-for-age, length-for-age or weight-for-length, classified as overweight or obese children. There is no association observed between nutritional status and household income, percentage of foods expenditure, and education level of fathers. A positive trend was observed between nutritional status of children and height of mothers A stronger positive trend was also observed for education level of mothers against nutritional status of the children. A significant (P<0.05) association between education of mothers and nutritional status (based on weight for age) of the children was demonstrated in these subjects. Conclusion: Level of education of mothers substantially contributed to nutritional status of children aged 12-36 months.Keywords: wellbeing families, nutritional status, determinant factors